One-step synthesis of Sc2W3O12:Eu3+ phosphors with tunable luminescence for WLED. Issue 8 (1st June 2019) - Li, Xinwei; Xu, Hualan; Xia, Xianming; Xie, Feiyan; Zhong, Shengliang; Xu, Dekang
Abstract: Sc2 W3 O12 is an important host matrix for rare-earth doped luminescence. However, the conventional method to prepare the material is solid-state reaction, which results into coarse and irregular morphologies. In this work, Eu 3+ doped Sc2 W3 O12 phosphors with high crystallinity and pure phase were successfully synthesized via one-step hydrothermal method. It was found that the crystalline phase changed from Sc2 W3 O12 phase to Na4 Sc2 (WO4 )5 phase when the molar ratio between Sc(NO3 )3 and Na2 WO4 decreased. The temperature-dependent X-ray diffraction analysis was performed to prove the negative thermal expansion property of Sc2 W3 O12 . A systematic study on the effect of reaction time, temperature and Eu 3+ doping concentration was explored. It was also found that the as-prepared samples displayed tunable emission colors, ranging from blueish white to orange red. Particularly, the white light emission with the chromaticity coordinate of (0.3395, 0.3289) can be realized in Sc2 W3 O12 : 5% Eu 3+ . What's more, the photoluminescence properties of the samples were investigated under different ambient temperatures between 97 and 280 K. The result clearly showed energy transfer between Eu 3+ and WO4 2− . The above results suggested that Sc2 W3 O12 :Eu 3+ can be excellent candidate for solid-state lasing, panel display and WLEDs.